Analisi Penyajian Laporan Keuangan di Perusahaan Food and Beverage yang Terdaftar di Bursa Efek Indonesia (BEI) Berdasarkan PSAK No.1 - Hilda Diana Safitri (JFAS : Journal of Finance and Accounting Studies, 2020)
This study aims to analyze how obedient and according to the presentation of financial statements of food and beverage companies listed on the Indonesia Stock Exchange in applying accounting standards namely PSAK NO.1 by using qualitative data analysis research techniques and obtaining data by documentation. Retrieval of the required data is obtained from the IDX website namely www.idx.co.id and there are 16 food and beverage subsector companies, data taken is the annual financial statements for the two periods that have been audited. the method of analysis of this study uses a method of comparing the company's financial statements with PSAK NO.1 format The results of this study are that 16 food and beverage companies listed on the Indonesia Stock Exchange have not fully complied with the Statement of Financial Accounting Standards, there are several components that are indeed not in accordance with the Statement of Financial Accounting Standards (PSAK).